Commemorating Baghel Singh's 'Conquest' of Delhi: The Fateh Diwas. (August 2020) - Singh, Kanika
This article examines the changing importance, in Sikh history, of Baghel Singh, a Sikh military commander in eighteenth-century Punjab, and the significance of the most recent events commemorating him in Delhi—the Fateh Diwas. The Fateh Diwas was a spectacular event organized for the first time in 2014 at the Red Fort in Delhi, by the Shiromani Akali Dal (SAD; Badal)-led Delhi Sikh Gurdwara Management Committee. It celebrated the conquest of Delhi by the Sikhs and the unfurling of the Sikh flag on the Red Fort by Baghel Singh. This claim is significant for its timing, symbolism and the historical legacy it seeks to remember. This representation of Baghel Singh also appears in modern paintings on Sikh history which are widely reproduced in popular spheres and also constitute the display in Sikh museums. A comparison of this particular representation of Baghel Singh with that in the nineteenth-century text, Sri Gur Panth Prakash by Ratan Singh Bhangu, is useful in understanding how Baghel Singh's role has changed in Sikh history and how is it being deployed in contemporary heritage politics.